A nomogram for predicting screw loosening after single-level posterior lumbar interbody fusion utilizing cortical bone trajectory screw: A minimum 2-year follow-up study - Zhang, Yiqi; Li, Yue; Hai, Yong; Guan, Li; Zhang, Xinuo; Pan, Aixing; Lu, Hongyi; Wu, Bingchao; Liu, Yuzeng (Frontiers in Surgery, 2022)
Purpose This study aims to investigate the risk factors for screw loosening after single-level posterior lumbar interbody fusion (PLIF) utilizing cortical bone trajectory (CBT) screw and establish a nomogram for predicting screw loosening. Methods A total of 79 patients (316 screws) who underwent single-level PLIF with CBT screw were included in the study. Preoperative, postoperative, and final follow-up demographic data, surgical data, and radiographic parameters were documented and analyzed to identify risk factors, and a predictive nomogram was established for screw loosening. The nomogram was assessed by concordance index (C-index), calibration plot, decision curve analysis (DCA), and internal validation. Results The incidence of screw loosening was 26.6% in 79 patients and 11.4% in 316 screws. Multifactorial regression analysis confirmed that fixed to S1 (FS1, OR = 3.82, 95% CI 1.12–12.71, P = 0.029), the coronal angle of the screw (CA, OR = 1.07, 95% CI 1.01–1.14, P = 0.039), and cortical bone contacted layers (CBCLs, OR = 0.17, 95% CI 0.10–0.29, P < 0.001) were risk factors and incorporated in the nomogram for predicting screw loosening after single-level PLIF with a CBT screw. The C-index of the nomogram was 0.877 (95% CI 0.818–0.936), which demonstrated good predictive accuracy. The calibration plot indicated an acceptable calibration of the nomogram that also had a positive benefit in guiding treatment decisions. Conclusion FS1, CA, and CBCLs are identified to be significant risk factors for screw loosening after single-level PLIF with the CBT technique. The nomogram we have established can be used to predict screw loosening and contribute to surgical decisions.